Pemberian Rekomendasi Hotel Berdasarkan Jarak di Kota Palangka Raya Berbasis Web - Christian, Efrans; Pranatawijaya, Viktor Handrianus; Sari, Nova Noor Kamala; Aprimikardo, Aprimikardo (Universitas Palangka Raya, 2022)
The City Government of Palangka Raya, in the year 2015 there was 2 4 star hotels, 2 star hotels 3 and 46 classy hotel jasmine in the City of Palangka Raya. Because of the increasing number of the construction of the hotel builted in the City of Palangka Raya, often cause problems for travelers that in doing a hotel search or specify the hotel based on the distance of the shortest path to the location of the hotel in the City of Palangka Raya with objective to minimize the cost of transportation and to speed up a journey.The research is made by using the algorithm of dijkstra to determine the path of the shortest distance to the location of the hotel destination in the City of Palangka Raya and software development methodologies in used in this research is using the waterfall method consists of five steps namely requirement analysis, design, coding, implementation and testing, and maintenance. Testing conducted in this study, namely to use blackbox testing to test the functions on the website that made.